Reduction of industrial noise in a metal-mechanical production process: Application of the Lean Six Sigma DMAIC methodology (2022)
The Six Sigma DMAIC methodology was applied to reduce noise in a metal-mechanical production process. In the definition stage, the workers were consulted, for the measurement stage, noise measurements were made for 10 days in four areas of the company, and 10 points reported by employees as potential sources of noise. The measurements showed that, on average, there were 7 points with a noise level higher than what is allowed by the standard, and the improvement actions established lower noise level averages in the different points. For the control stage, a test of means was performed with paired samples, which showed that the decrease in points was significant, although after the improvement, the milling machine and the polishing machine continued to have noise level averages above the values allowed.